The image of the hero in modern Ukrainian cinema. Interview with Anastasia Karpenko - Tymoshenko, Alyona (Ukrainian Cultural Studies, 2024)
Anastasia Karpenko is a popular Ukrainianfilm and theatre actress.  She receivedthe Best Actress award from the Ciné+ jury at the 75th InternationalInternational Film Festival in Locarno for her role in the film How is Katya? ’, actressKyiv Academic Theatre of Drama and Comedy on the left bank of the Dnipro River.